Degradation of Shanxi lignite by Trichoderma citrinoviride. (1st May 2021) - Feng, Xin; Sun, Jinghong; Xie, Yuhong
Highlights: The A-1 strain solubilized 35% (by weight) of Shanxi lignite within 20 days. The A-1 fungal strain had the ability of dehydroxylate and demethylate. The extracellular enzyme is the key to the biodegradation mechanism of lignite. The degradation mechanism was the combination of multiple extracellular enzymes. Abstract: A fungal isolate A-1, identified as Trichoderma citrinoviride by sequencing of the 26S rDNA D1/D2 region, was isolated from the seeds of white Tremella. This fungus was used to degrade the Shanxi lignite. The intensity of the bio-solubilization was determined by measuring the weight loss of the lignite gravimetrically. This fungus solubilized 35% (by weight) of Shanxi lignite after H2 O2 pretreatment within 20 days. The enzyme activity analysis showed that the fungus could produce oxidase, lignin peroxidase, and laccase. The degradation mechanism of the fungus was the combined action of multiple extracellular enzymes, which achieved a high degradation efficiency. The lignite and the bio-solubilization products were characterized by ultraviolet spectroscopy (UV), infrared spectroscopy (FT-IR), gas chromatography-mass spectrometry (GC–MS), and X-ray diffraction (XRD). Results showed that the A-1 fungal strain had the abilities of dehydroxylation and demethylation, as well as breaking the side chains of the aromatic rings. After coal degradation, the solid residue mainly contains organic functional groups such as hydroxyl, aromatic ring, and esters, and the liquid product contains aliphatic compounds such as alkanes, alcohols, esters, and phenolic organics. The main characteristic peaks of lignite were quartz (SiO2 ) and calcite (CaCO3 ). The relevant characteristic peaks of CaCO3 disappear after the coal sample was pretreated with H2 O2, indicating that the pretreatment process relaxed the interaction between coal macromolecules and improved the microbial degradation ability of coal. Trichoderma citrinoviride A-1 can promote biodegradation, and the extracellular enzyme contained in this fungus is the key to the biodegradation mechanism of lignite.